2020
DOI: 10.1002/jdn.10039
|View full text |Cite
|
Sign up to set email alerts
|

Brain tissue volumes at term‐equivalent age are associated with early motor behavior in very preterm infants

Abstract: Preterm birth is associated with a wide range of adverse developmental outcomes, including sensory, motor, cognitive and language impairments, and behavioral or attention problems. Subtle motor deficits that might emerge in premature infants with no evident or with mild brain injury encompass qualitative and quantitative aspects of motor behavior. This prospective cohort study provided an evaluation of the relationship between brain tissue volumes revealed by magnetic resonance imaging (MRI) at term‐equivalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“… 43 , 45 , 46 Early quantitative measurements of the cerebellum have been associated with motor behavior during the first 2 years of life, as well as cognitive development; however, further studies are required to elucidate the exact role of a reduced size of the cerebellum. 47 50 …”
Section: Discussionmentioning
confidence: 99%
“… 43 , 45 , 46 Early quantitative measurements of the cerebellum have been associated with motor behavior during the first 2 years of life, as well as cognitive development; however, further studies are required to elucidate the exact role of a reduced size of the cerebellum. 47 50 …”
Section: Discussionmentioning
confidence: 99%
“…According to the radial vulnerability hypothesis elaborated by Kostović and colleagues axonal pathways are the most vulnerable during the most intense phase of their growth (Katušić et al, 2020;Kostović et al, 2014Kostović et al, , 2021. Altered microstructural development of fronto-limbic pathways-and particularly of the uncinate fasciculus-has been found in association with maternal stress and anxiety during pregnancy (Dean et al, 2018;Lautarescu, Pecheva, et al, 2020;Posner et al, 2016;Rifkin-Graboi et al, 2015;Sarkar et al, 2014;VanTieghem & Tottenham, 2017).…”
Section: Maternal Anxiety-driven Modulation Of Fetal Functional Conne...mentioning
confidence: 99%
“…Some studies have investigated the relationship between structural brain alterations at TEA and neurodevelopmental outcome in children born too soon (Gui et al., 2019 ; Keunen et al., 2016 ; Moeskops et al., 2017 ). A recent study demonstrated a relationship between brain tissue volumes at TEA and early motor behavior in VPT infants (Katušić et al., 2020 ). In addition, Lind et al.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have investigated the relationship between structural brain alterations at TEA and neurodevelopmental outcome in children born too soon (Gui et al, 2019;Keunen et al, 2016;Moeskops et al, 2017). A recent study demonstrated a relationship between brain tissue volumes at TEA and early motor behavior in VPT infants (Katušić et al, 2020). In addition, Lind et al (2010) demonstrated significant associations between smaller volumes of total brain tissue and poorer executive functions, between smaller cerebellar volumes and both poorer executive functions and motor skills, as well as between larger brainstem volume and poorer language functions.…”
Section: Introductionmentioning
confidence: 99%